2021
DOI: 10.1016/j.ijid.2020.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine Safety Outcome within Approved Therapeutic Protocol for COVID-19 Outpatients in Saudi Arabia

Abstract: Highlights This study is the first conducted national study in Saudi Arabia discussing the safety outcome of hydroxychloroquine during COVID-19 pandemic. Data were always cross-matched with national database across the Kingdom of Saudi Arabia. The study targeted outpatients setting and patients with mild to moderate cases of COVID-19. Not in hospitalised patients. Results showed that hydroxychloroquine was well tolerated and with very mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A retrospective longitudinal cohort study showed that hydroxychloroquine treatment (OR 3.891, 95% CI 1.196–12.653) was associated with renal function recovery in patients with lupus nephritis 34 . A large-sampled multicentered observational study has shown that the exposure of hydroxychloroquine is associated with a decreased risk of hospitalization from COVID-19 (OR 0.53; 95% CI 0.29–0.95) 35 . Additional, findings from some recent random-controlled studies raise the concern about whether dexamethasone treatment could improve the outcome of COVID-19 36 , 37 Whether patients with higher sCys C levels might benefit form early hospital treatment measures such as hydroxychloroquine or dexamethasone need to be addressed in future large-scale studies.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective longitudinal cohort study showed that hydroxychloroquine treatment (OR 3.891, 95% CI 1.196–12.653) was associated with renal function recovery in patients with lupus nephritis 34 . A large-sampled multicentered observational study has shown that the exposure of hydroxychloroquine is associated with a decreased risk of hospitalization from COVID-19 (OR 0.53; 95% CI 0.29–0.95) 35 . Additional, findings from some recent random-controlled studies raise the concern about whether dexamethasone treatment could improve the outcome of COVID-19 36 , 37 Whether patients with higher sCys C levels might benefit form early hospital treatment measures such as hydroxychloroquine or dexamethasone need to be addressed in future large-scale studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies especially RCTs demonstrated that HCQ can be administrated safely and without incidence of serious cardiac adverse events in outpatients and hospitalized patients with mild COVID-19. [14] , [28] , [29] , [30]…”
Section: Discussionmentioning
confidence: 99%
“…However, with the publication of subsequent studies, this concern has been somewhat alleviated. [6] , [13] , [14] Taken together, these factors once again led to attention being paid to HCQ use in outpatient settings.…”
Section: Introductionmentioning
confidence: 99%
“…In practical applications, different data sources (literature) may lead to controversial statistical analysis results. For example, hydroxychloroquine has been increasingly found to be useless in the treatment of COVID-19 [77], but many studies, especially early stage studies, include a description that it is a potential and safe drug [78][79][80]. Therefore, data preprocessing is critical to the quality of RE results.…”
Section: Principal Findingsmentioning
confidence: 99%